Granulomatosis with Polyangiitis (Wegener Granulomatosis) Mimicking Infective Endocarditis - Imène Rachdi (European Journal of Case Reports in Internal Medicine, 2014)
Introduction Infective endocarditis (IE) has been reported to mimic granulomatosis with polyangiitis (GPA) and to test positive to antineutrophil cytoplasmic antibodies (ANCA), which may lead to a misdiagnosis and inappropriate treatment.